2016
DOI: 10.17159/2309-8309/2016/v15n3a2
|View full text |Cite
|
Sign up to set email alerts
|

Short-term results of grade III open tibia fractures treated with circular fixators

Abstract: Grade III open tibia fractures have previously been shown to have high infection and non-union rates, and the optimal treatment remains controversial. We present the short-term results of 94 consecutive Gustilo-Anderson grade III open tibia fractures, definitively treated with circular external fixators in this retrospective study. A total of 94 patients (80 males and 14 females), with a mean age of 36.5 years (range 8-73) were followed up for a mean period of 12 months (range 6-52). Deep infection occurred in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…The rate of chronic osteomyelitis following Gustilo-Anderson IIIB fractures in our study was 1.4%. This compares favourably to 31,38,40,42 Our data failed to show any statistically significant complications in patients infected with HIV. The final outcomes were also not affected by HIV infection.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The rate of chronic osteomyelitis following Gustilo-Anderson IIIB fractures in our study was 1.4%. This compares favourably to 31,38,40,42 Our data failed to show any statistically significant complications in patients infected with HIV. The final outcomes were also not affected by HIV infection.…”
Section: Discussionsupporting
confidence: 58%
“…Our results are comparable to results quoted in international literature. [32][33][34][35][36][37][38][39] The relatively low rate of failed limb salvage (our amputation rate was 1%) observed in our study points to the fact that ring fixation is a safe and effective treatment modality. It may also indicate a relatively conservative approach to patient selection for limb salvage and that our unit could consider a more aggressive approach in attempting limb salvage instead of early amputation.…”
Section: Discussionmentioning
confidence: 49%
“…15 These findings were echoed by Niewoudt et al, who noted that HIV did not appear to be associated with an increased risk of deep infection or non-union in grade III open tibia fractures treated with circular external fixation. 16 The influence of CD4 count on the development of infection also remains unclear. Guild et al, showed an increased infection rate in patients with a CD4 count below 300.…”
Section: Discussionmentioning
confidence: 99%
“…96 Circular external fixation has demonstrated its effectiveness in the management of complex open tibia fractures in both civilian and war injuries. [97][98][99][100] They utilise indirect reduction techniques with fine wires and/or half pins and small incisions, which ensure minimal soft-tissue damage and soft-tissue footprint. 4 Treatment with circular external fixation, which does not place any hardware at the fracture site, may reduce infections and hospital readmissions.…”
Section: Skeletal Stabilisationmentioning
confidence: 99%
“…Nieuwoudt et al reported excellent short-term results with low infection and non-union rates on 94 consecutive grade III open tibia fractures treated with circular external fixation followed up for a period of 12 months. 100 The majority of patients were treated in traditional Ilizarov fixators. Hexapod external fixators were used in 12 patients.…”
Section: Skeletal Stabilisationmentioning
confidence: 99%